Protection of Celebrity Rights under IPR Regime in India (Journal of Intellectual Property Rights (JIPR), 2024)
With the emergence of the numerous forms of mass media, various social platforms, and the ever-increasing trend of advertisements have led to the invasion of the privacy of celebrities and the exploitation of their goodwill.1 The celebrity possesses various rights such as the right to privacy, personality rights, merchandising rights, and publicity rights. Celebrities hold goodwill in the market and are granted to make wealth out of their identity. 2 Celebrity endorsements are the most common way of earning riches by celebrities using their name and fame. Therefore, the rights of the celebrities are unique and are more like a property of the celebrity which can be exclusively enjoyed by them. As there is a property, there can be cases of unapproved trespass3 using misappropriation of their goodwill and the privacy breach of the celebrities. Such unapproved trespass demands legal protection to protect celebrities' unique and intangible rights. The protection for the rights of the celebrities is at a nascent stage in India, also the statutory provisions under the intellectual property rights (IPR) regime are inadequate to grant complete protection to the celebrities. Accordingly, the present study aims to analyse various rights granted to celebrities and determine the legal means to protect those rights.